Live culture-based qPCR screening of Taq DNA polymerase variants for resistance to PCR inhibitors - Kermekchiev, Milko B.; Zhang, Zhian; Barnes, Wayne M. (Frontiers in Bioengineering and Biotechnology, 2025)
We present a live culture PCR (LC-PCR) workflow that enables direct screening of randomly mutagenized Thermus aquaticus (Taq) and Klentaq1 DNA polymerase libraries without enzyme purification. Intact bacterial cells expressing individual variants serve as both enzyme source and DNA template in real-time PCR, allowing rapid selection for inhibitor resistance in a 96-well format. Screening ~14,000 clones in the presence of potent inhibitors (chocolate, black pepper) yielded two novel variants—Taq C-66 (E818V) and Klentaq1 H101 (K738R)—with superior resistance to diverse PCR inhibitors, including blood, humic acid, and plant extracts, compared to wild-type and previously known resistant mutants. Resistance persisted after purification, indicating intrinsic enzymatic tolerance. Structural mapping suggests these substitutions may enhance nucleotide binding or stabilize the polymerase—DNA complex, reducing susceptibility to inhibitor interference. LC-PCR reduces screening time, cost, and contamination risk, and is readily adaptable for evolving polymerases with enhanced speed, fidelity, or substrate versatility.